Acceptability of a long‐acting injectable HIV prevention product among US and African women: findings from a phase 2 clinical Trial (HPTN 076). Issue 10 (25th October 2019) - Tolley, Elizabeth E; Li, Sue; Zangeneh, Sahar Z; Atujuna, Millicent; Musara, Petina; Justman, Jessica; Pathak, Subash; Bekker, Linda‐Gail; Swaminathan, Shobha; Stanton, Jill; Farrior, Jennifer; Sista, Nirupama
Abstract: Introduction: High HIV incidence and low adherence to daily oral PrEP among women underscore the need for more acceptable and easier to use HIV prevention products. Global demand for injectable contraception suggests that new, long‐acting, injectable formulations could meet this need. We examine acceptability of a long‐acting injectable PrEP among HIV‐uninfected women in Zimbabwe, South Africa and two United States phase 2 trial sites. Methods: Quantitative surveys were administered at the first, fourth and sixth injection visits. Focus group discussions (FGD) were conducted after the sixth injection visit. We compared the acceptability of injectable product attributes, prevention preferences and future interest in injectable PrEP by site and arm and ran longitudinal ordinal logistic regression models to identify determinants of future interest in injectable PrEP. Results: Between April 2015 and February 2017, the trial enrolled 136 (100 African, 36 US) women with a median age of 31 years. Most participants (>75%) rated injectable attributes as very acceptable. While few reported rash or other side effects, 56% to 67% reported injection pain, with nonsignificant differences over time and between arms. During FGDs, participants described initial fear of the injectable and variable experiences with pain. Most US and African participants preferred injectable PrEP to daily oral pills (56% to 96% vs. 4% to 25%). Future interest in using injectable PrEP was associated with acceptability of product attributes and was higher in African than US sites. In FGDs, participants described multiple reasons for trial participation, including a combination of monetary, health‐related and altruistic motivations. While associated with future interest in use in univariate models, neither altruistic nor personal motivations remained significant in the multivariate model. Conclusions: This study found that long‐acting injectable PrEP is acceptable among African and US women experiencing product use. Acceptability of product attributes better predicted future interest in injectable use than experience of pain. This is reassuring as a single‐dose regimen of a different product has advanced to phase 3 trials. Finally, the study suggests that future demand for an injectable PrEP by women may be greater in African than US settings, where the risk of HIV is highest.